'Be bold, courageous and wise'; Post-war reconstruction in the city of Exeter - Maudling, Clare (International Planning History Society Proceedings, 2016)
The city of Exeter sustained extensive bomb damage during the Second World War, suffering a total of 18 air raids between 1940 and 1942. Exeter was designated as a blitzed city and encouraged to produce a comprehensive reconstruction plan. The resultant plan, Exeter Phoenix, was initially praised and welcomed by traders and citizens. However, it was not fully executed and later became the subject of derision. The Exeter Phoenix has been the subject of a small number of studies which have cited trader pressure and financial constraints as the reasons for the alterations, while the rebuilt central area has been criticised for its architecture, design and poor architectural control. However, it is notable that these studies have not examined the local records in any detail. As a result various factors which led to changes in Sharp’s plan have been overlooked, as have the methods which the City Council used to control the architectural treatment of the new buildings. This paper examines the city’s use of leases as method of architectural control and the handling of trader discontent in order to execute the plan. External factors such as governmental guidelines are also indicated as factors for changes in the plan.